Decremento de uso de equipo de seguridad industrial y su relación con la accidentabilidad en proyectos de construcción. - Llanga Puluchi, Viviana Alexandra (2017)
The management of occupational health and safety and high accident rates are common problems that arise in the field of construction, which means a serious problem. The activities performed within a work, due to the nature of the work presented in the day to day, make this occupational field dangerous, so it is important to look for ways to safeguard the integrity of workers and reduce risks which generate the construction activities. The lack of attention given to the good use and handling of industrial safety equipment has led to problems in terms of accidents, which are evident in injuries and even greater effects such as loss of life. The purpose of this investigation was to determine the decreases in the use of industrial safety equipment and to establish if there is a relationship with the accident, for which a methodology was developed based on the use of a dron through which the information was raised in video and photograph of the use of industrial safety equipment in the workers of a private company. With the data collected, it was possible to quantify the total clothing worn by each worker in the hours inspected and then determine the percentage of decreases in the use of industrial safety equipment. Due to the fact that the present investigation was carried out in a road project, its development is pending for other type of jobs.